Diseño de un siistema de control interno para la Orquesta Sinfónica de Loja - Terán Lozano, Ana Belén (2017)
The research project called "Design of an Internal Control System for the Loja Symphonic Orchestra", is developed according to the stated objectives, such as: To gather information on the theoretical references of internal control related to the Institution, with the purpose of Adopt measures to safeguard resources, as well as diagnose the current situation of the Loja Symphony Orchestra on the handling and process of internal control; And design internal control procedures to promote the efficiency of operations. For the accomplishment of this work was necessary the application of materials and methods that allowed the compilation of information regarding the Internal Control and through the interviews applied to the Executive Director to the Chief Financial Officer and the Human Resources Analyst of the Institution was obtained As a result of data that served to implement the proposal, once the objectives were met, it was determined that the Loja Symphony Orchestra lacks an Internal Administrative and Financial Control System that allows it to carry out an adequate control of the operations carried out by the Institution, therefore it can be established that it is not complying with the Internal Control Norms issued by the Comptroller General of the State in which it is mentioned that each institution will elaborate control procedures that allow the proper functioning of the same. 5 As an alternative solution to the shortcomings encountered, a Design of Internal Control and Financial Control Procedures was developed that would contribute to institutional development, safeguarding the resources, ensuring the correctness and fidelity of the registry for the fulfillment of objectives; It should be emphasized that it is the duty of the Directors to structure procedures to enable them to maintain adequate control over the operations carried out. These procedures were elaborated in accordance with the Internal Control Standards for Entities, Public Sector Organizations and Private Law Entities with Public Resources; And applied to the most significant aspects presented by the Institution, which are easy to apply and will serve as a guide in the development of activities